UTILISATION OF THE FINANCIAL SYSTEM AND PROFILE WEBSITE OF THE AL-KHOIRIYAH MOSQUE BANYU URIP - Teguh Herlambang; Firman Yudianto; Mukhtar Adinugroho; Maisyatul Fikriyyah; Wahyu Wiji Lestari; Diah Ayuningtyas Wati (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
This PPM report aims to provide an effective solution in overcoming the main problems faced in the process of recording Infaq Reports and going in and out of the mosque treasury, namely the Al Khoiriyah Mosque. The manual recording process takes quite a lot of time and uses a ledger to write down incoming cash flows. Apart from that, the problem of conveying information is still simple. The specific goals and targets to be achieved in this community service activity are the Implementation of the Al Khoriyah Mosque Financial System: The Al Khoiriyah Mosque Financial System will be used by the Al Khoiriyah Mosque to record financial reports such as infaq reports and incoming and outgoing mosque cash funds. This system replaces the manual method of using the mosque cash book which is currently used. The methods that will be used to achieve goals and targets are information collection, financial system preparation, outreach or training, evaluation and system improvement.